PRELIMINARY PROTEIN PROFILING OF COPPER AND ZINC TREATED LACTOBACILLUS RHAMNOSUS: Life Science-Microbiology - SREEMANTHULA, SREEVANI; SEKHAR KATHERA, CHANDRA; KUMARI JASTI, PRAMODA (International Journal of Life Science and Pharma Research, 2013)
Toxic metals are a class of elements with no biological role but with extreme toxicity. Humans, plants and also beneficial microbes suffers from metal toxicity. Probiotic bacteria are very beneficial to humans and animals due to their antipathogenic potential. Probiotic bacteria have become anintegral elements to everyday healthy living. The aim of this study was to determine the preliminary protein profiling of Zinc and Copper influenced Lactobacillus rhamnosus MTCC 1408 by using the techniques SDS-PAGE and 2-D PAGE. The results shown that the protein profiles of Copper stressed proteins showed significant difference when compared to the Zinc stressed proteins.